Investigation of the Plasticity and Bearing Capacity of Beach Sand-Stabilized Clay under Different Soaking Durations - Annisa, Humairah; Ibrahim, Zulfadli; Yunus, Ilham; Fitriyanti; Basri, Muh. Subri (Universitas Muslim Indonesia, 2025)
Clay soils are widely recognized for their unfavorable geotechnical properties, including high plasticity and low bearing capacity, which often compromise the performance of subgrades and foundations. Conventional stabilizers such as cement and lime are effective but limited by cost and environmental concerns. Beach sand with its non-plasticity, density, and high internal friction angle, offers potential as a natural stabilizer. This study investigates the stabilization of clay soil using Kupa beach sand (KBS) under various soaking durations. The evaluation focuses on compaction and CBR tests to determine the bearing capacity, as well as Atterberg limit tests to assess the plasticity of the stabilized samples. The findings show that incorporating 30% Kupa beach sand optimally improves engineering properties, reducing the Plasticity Index (PI) from 40,94% to 6,18% and significantly increasing CBR value from 7,638% (KBS0%) to 38,227% (KBS30%) under unsoaked conditions. Although prolonged soaking reduced CBR values due to weakened particle bonding, the stabilized mixture retained higher CBR value (20,672%) than untreated clay (3,546%) after 21 days, indicating durability under saturated conditions. These results confirm that beach sand effectively decreases plasticity, enhances strength, and mitigates moisture susceptibility.